Dostopnost Ustave RS za ljudi z motnjami v duševnem razvoju – dileme in izzivi - Jakšić Ivačič, Živa; Kadunc, Barbara; Mlakar, Špela; Schmid, Špela (Slavia Centralis, 2020)
Accessibility of the Constitution of the Republic of Slovenia for persons with intellectual disabilities – dilemmas and challengesThe Convention on the Rights of Persons with Disabilities requires that all information is accessible to people with disabilities in an understandable form. The purpose of the paper is to evaluate the process of transforming the Constitution of the Republic of Slovenia into an easy-to-read and understandable form and verification of four articles, emphasizing the involvement of eight proofreaders with intellectual disabilities. Four Articles of the Constitution were adapted in two versions. We found that proofreaders want all the information from the original text of the article, written in an understandable way. They expressed the desire to have an interpretative version of the Article next to the adapted version of article, written in easy-to-read form.
Keywords: Convention on the Rights of Persons with Disabilities; Constitution of the Republic of Slovenia; easy-to-read; proofreaders; intellectual disabilities